Nanovesicles as Potential Carriers for Delivery of Antiviral Drugs: A Comprehensive Review - Bindhani, Sabitri; Nayak, Amit Kumar (Current Drug Delivery, 2025)
Different nanocarriers-based strategies are now extensively being used as an important strategy for improving drug efficacy and responsiveness, reducing toxicity issues related to drugs and harmful side effects, and overcoming the numerous significant difficulties related to absorption and bioavailability. Amongst different nanocarriers, nanovesicles are excellent and versatile systems for effectively delivering therapeutic agents, targeting ligand distribution and location. Nanovesicles are nanosized self-assembling spherical capsules with an aqueous core and one/more lipid(s) layers. Several synthetic nanovesicles have been developed and investigated for their prospective uses in delivering drugs, proteins, peptides, nutrients, etc. Important procedures for nanovesicle manufacturing are thin-film hydration, unshaken method, ethanol injection, ether injection, proliposomes, freeze-drying, hot method, cold method, reverse-phase evaporation, and ultrasonication. Liposomes, liposomes, ethosomes, exosomes, and transferosomes (elastic vesicles) are the nonvesicular candidates extensively investigated to deliver antiviral drugs. This review article comprehensively overview different nanovesicles, their compositions, manufacturing, and applications as potential carriers for effectively delivering different antiviral drugs to treat viral diseases.
Keywords: liposomes